Chronic inflammation and progression of chronic kidney disease in patients with type 2 diabetes - Mazur, T.; Demikhova, N.; Rudenko, T.; Yurchenko, A.; Yezhova, O.; Bokova, S.; Demikhov, A. (Ukrainian Journal of Nephrology and Dialysis, 2021)
Chronic inflammation, atherosclerosis, tubulointerstitial fibrosis, and vascular damage play a crucial role in the progression of chronic kidney disease (CKD) in patients with type 2 diabetes mellitus (DM). However, specific biomarkers that can determine the progression of diabetic kidney disease, including patients with minimal albuminuria, remain undefined. The present study aimed to determine markers of chronic inflammation as indicators of CKD progression in patients with type 2 DM. Methods. 45 patients with type 2 DM and stage 1-3 CKD were involved in this cross-sectional observational study. Analysis of cellular mechanisms of CKD progression was performed on the concentrations of endothelin-1 (ET-1), fibronectin (FN), tumor necrosis factor-alpha (TNF-α), transforming growth factor beta-1 (TGF-β1), and monocyte chemoattractant protein (MCP) -1) in the serum. Results. In patients with type 2 DM, an increasing trend in the majority of endothelial and proinflammatory mediators was found according to the CKD stages despite normal albuminuria. Conclusions. Concentrations of TNF-α, ET, TGF-β1 and MCP-1 can be used to assess the progression of CKD in patients with type 2 DM with normal albuminuria. Further researches are needed to determine early indicators of diabetic kidney disease progression.